Intra‐subject variability in muscle activity and co‐contraction during jumps and landings in children and adults - Raffalt, P. C.; Alkjær, T.; Simonsen, E. B. (Scandinavian journal of medicine & science in sports, 2017)
We investigated muscle activity, intra‐subject variability in muscle activity and co‐contraction during vertical jumps and landings in children and adults. Ten male children and 10 male adults completed 10 countermovement jumps (CMJ), 10 drop jumps (DJ) from 30 cm, 10 low and high landings from 30 and 60 cm for the children and 60 and 90 cm for the adults. The adults also performed ten DJ from 60 cm. EMG was recorded from nine lower limb muscles in the right leg and normalized to isometric MVC. Statistical parametric mapping was used to reveal differences in the muscle activity and intra‐subject variability in the muscle activity. Co‐contraction was quantified for two thigh muscle pairs and one plantar flexor/dorsiflexor muscle pair and group differences were assessed (two‐way ANOVA). No significant differences were observed in the less eccentric demanding CMJ while significantly higher muscle activity magnitude and intra‐subject variability were observed for the children during the initial part of the contact phase of DJ and landings, indicating a less consistent muscle activity pattern in the children. This may indicate that vertical jumps/landings involving a high amount of eccentric muscle contraction constrain the muscle activation in children, possibly because of immature motor control.